Pengaruh Quality Of Work Life dan Employee Engagement terhadap Organizational Citizenship Behavior (OCB) dengan Moderasi Resistance To Change (Studi Pada Pegawai Dinas Pendidikan Kota Semarang) - Laksmintari Dewi Paramitha; Tristiana Rijanti (Jurnal Mirai Management, 2022)
Abstract The purpose of the study was to analyze and describe the effect of Quality of Work Life and Employee Engagement on Organizational Citizenship Behavior (OCB) Employees of the Semarang City Education Office. To analyze and describe resistance to change moderate the influence of Quality of Work Life and Employee Engagement on Organizational Citizenship Behavior (OCB) Employees of the Semarang City Education Office. The population in this study was ASN Semarang City Education Office, totaling 97 employees. The sample in this study was ASN Semarang City Education Office, totaling 97 employees. Sampling with a sampling census technique of 97 employees. Data collection methods using a questionnaire. Data analysis using linear regression analysis. Based on the results of the study, it can be concluded that the quality of work life has a positive effect on Organizational Citizenship Behavior (OCB) Employees of the Semarang City Education Office. Employee engagement has a positive effect on Organizational Citizenship Behavior (OCB) employee of the Semarang City Education Office. Resistance to change moderate the influence of the quality of work life on Organizational Citizenship Behavior (OCB) Employees of the Semarang City Education Office. Resistance to change moderates the effect of employee engagement on Organizational Citizenship Behavior (OCB) Employee of the Semarang City Education Office. Keywords: Quality of Work Life, Employee Engagement, Resistance to Change and Organizational Citizenship Behavior Abstrak Tujuan penelitian adalah untuk menganalisis dan mendeskripsikan pengaruh Quality of Work Life dan employee engagement terhadap Organizational Citizenship Behavior (OCB) pegawai Dinas Pendidikan Kota Semarang. Untuk menganalisis dan mendeskripsikan resistance to change memoderasi pengaruh Quality of Work Life dan employee engagement terhadap Organizational Citizenship Behavior (OCB) pegawai Dinas Pendidikan Kota Semarang. Populasi dalam penelitian ini adalah ASN Dinas Pendidikan Kota Semarang yang berjumlah 97 pegawai. Sampel dalam penelitian ini adalah ASN Dinas Pendidikan Kota Semarang yang berjumlah 97 pegawai. Pengambilan sampel dengan teknik sensus sampling sejumlah 97 pegawai. Metode pengumpulan data menggunakan kuesioner. Analisis data menggunakan analisis regresi linier. Berdasarkan hasil penelitian dapat disimpulkan Kualitas kehidupan kerja berpengaruh positif terhadap Organizational Citizenship Behavior (OCB) pegawai Dinas Pendidikan Kota Semarang. Employee engagement berpengaruh positif terhadap Organizational Citizenship Behavior (OCB) pegawai Dinas Pendidikan Kota Semarang. Resistance to change memoderasi pengaruh kualitas kehidupan kerja terhadap Organizational Citizenship Behavior (OCB) pegawai Dinas Pendidikan Kota Semarang. Resistance to change memoderasi pengaruh Employee engagement terhadap Organizational Citizenship Behavior (OCB) pegawai Dinas Pendidikan Kota Semarang. Kata kunci : Quality of Work Life, employee engagement, Resistance to change dan Organizational Citizenship Behavior.